Interpreting Adjuncts: Processing English As-Clauses. (March 2022) - Frazier, Lyn; Clifton, Charles
Four experiments probed the interpretation of sentence-final as -clauses (e.g., Close the book as a librarian would/would do) ambiguous between a manner interpretation and a "propositional" interpretation. Experiment 1, an interpretation study, found a predominance of manner interpretations for sentences containing would and would do as the elliptical predicate inside the as -clause, biased by which form participants were initially exposed to. In Experiment 2, we assumed that a comma may be present before the as -clause for both interpretations, but that when the contrast between a comma and no comma is called to the reader's attention it will favor the propositional interpretation. The expectation was confirmed. In Experiment 3 a would -sentence was preceded by a How question or by a What's with question: propositional interpretations were rare but more prevalent following the What's with question than the manner question. Experiment 4 added a What did question and tested both no-comma would (NoComma) sentences and comma would do (CommaDo) sentences. CommaDo sentences received more propositional interpretations than NoComma sentences, and were read faster following the What's with question than the How question, whereas the NoComma were read faster after the How question. All four studies showed manner interpretations prevail, though would do, a (contrastive) comma or a non-manner question increase the frequency of propositional interpretations. Two possibilities are considered for what underlies the manner preference: a general preference for an adjunct to be part of the event description in cases of ambiguity, or the availability of a pre-existing event-"slot" for manner. The reading time results favor the former possibility.